Prework Book Maths Activity (2022)
Math skills are so important and fun to teach to preschoolers.‘My Activity – Maths Book’ is a quick preschool activity book to teach kids to identify numbers, count, and even colouring. • Perfect activity book for kids ages 2-5• Full colourful pages• Hands-on activities to teach early math concepts• Charming pictures • Best for building fine motor and recognition skills• A great gift for toddlers Most suitable for early learners, this 32 pages book is a fun way to practice number recognition. Perfect age-appropriate activities will keep the tiny tots entertained for hours.